Dendritic cells control T cell tonic signaling required for responsiveness to foreign antigen - Hochweller, Kristin; Wabnitz, Guido H.; Samstag, Yvonne; Suffner, Janine; Hämmerling, Günter J.; Garbi, Natalio (Proceedings of the National Academy of Sciences of the United States of America, 2010)
Dendritic cells (DCs) are key components of the adaptive immune system contributing to initiation and regulation of T cell responses. T cells continuously scan DCs in lymphoid organs for the presence of foreign antigen. However, little is known about the functional consequences of these frequent T cell-DC interactions without cognate antigen. Here we demonstrate that these contacts in the absence of foreign antigen serve an important function, namely, induction of a basal activation level in T cells required for responsiveness to subsequent encounters with foreign antigens. This basal activation is provided by self-recognition of MHC molecules on DCs. Following DC depletion in mice, T cells became impaired in TCR signaling and immune synapse formation, and consequently were hyporesponsive to antigen. This process was reversible, as T cells quickly recovered when the number of DCs returned to a normal level. The extent of T cell reactivity correlated with the degree of DC depletion in lymphoid organs, suggesting that a full DC compartment guarantees optimal T cell responsiveness. These findings indicate that DCs are specialized cells that not only present foreign antigen, but also promote a “tonic” state in T cells for antigen responsiveness.
Gesehen am 24.05.2023